2011
DOI: 10.1101/gr.133009.111
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of long noncoding RNAs expressed during zebrafish embryogenesis

Abstract: Long noncoding RNAs (lncRNAs) comprise a diverse class of transcripts that structurally resemble mRNAs but do not encode proteins. Recent genome-wide studies in humans and the mouse have annotated lncRNAs expressed in cell lines and adult tissues, but a systematic analysis of lncRNAs expressed during vertebrate embryogenesis has been elusive. To identify lncRNAs with potential functions in vertebrate embryogenesis, we performed a time-series of RNA-seq experiments at eight stages during early zebrafish develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
836
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 739 publications
(925 citation statements)
references
References 66 publications
(129 reference statements)
85
836
0
4
Order By: Relevance
“…However, the total number of lincRNAs (<200) was still far below the number of reported lincRNAs (550 to ;8000) in animals (Guttman et al, 2009(Guttman et al, , 2010Khalil et al, 2009;Cabili et al, 2011;Ulitsky et al, 2011;Pauli et al, 2012). Assuming that a large number of lincRNAs may still remain undiscovered in Arabidopsis, we developed a bioinformatics strategy to identify lincRNAs on a genome-wide basis.…”
Section: Previously Characterized Lincrnas In Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the total number of lincRNAs (<200) was still far below the number of reported lincRNAs (550 to ;8000) in animals (Guttman et al, 2009(Guttman et al, , 2010Khalil et al, 2009;Cabili et al, 2011;Ulitsky et al, 2011;Pauli et al, 2012). Assuming that a large number of lincRNAs may still remain undiscovered in Arabidopsis, we developed a bioinformatics strategy to identify lincRNAs on a genome-wide basis.…”
Section: Previously Characterized Lincrnas In Arabidopsismentioning
confidence: 99%
“…Average signal values of two independent flower samples are given. Ulitsky et al, 2011;Pauli et al, 2012). We aligned RNA sequences to TAIR9 using Tophat and SAMtools (Trapnell et al, 2009).…”
Section: Identification and Verification Of Lincrna By Rna Sequencingmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) have important regulatory functions and they have become a hot research field in recent years (Cabili et al, 2011;Chen et al, 2011c;Derrien et al, 2012;Fan and Zhang, 2015;Lee and Kikyo, 2012;Pauli et al, 2012). In the past decades, researchers mainly focused on exploring the functions of protein-coding genes, but neglected an important category of genes called lncRNAs.…”
Section: Identifying Long Noncoding Rnasmentioning
confidence: 99%
“…RNA-seq provides unprecedented opportunities for exploring those novel lncRNAs. Some studies identified a number of novel lncRNAs based on the RNA-seq data in different organisms including humans (Cabili et al, 2011), mouse (Guttman et al, 2010) and zebrafish (Pauli et al, 2012). A popular way to identify lncRNAs is to conduct transcriptome reconstruction using genome-guided methods (such as Cufflinks (Trapnell et al, 2010)) first (Figure 4).…”
Section: Identifying Long Noncoding Rnasmentioning
confidence: 99%
See 1 more Smart Citation